Hovenia dulcis Thunb Extract and Its Ingredient Methyl Vanillate Activate Wnt/β-Catenin Pathway and Increase Bone Mass in Growing or Ovariectomized Mice - Cha, Pu-Hyeon (Public Library of Science, 2014)
The Wnt/β-catenin pathway is a potential target for development of anabolic agents to treat osteoporosis because of its role in osteoblast differentiation and bone formation. However, there is no clinically available anti-osteoporosis drug that targets this Wnt/β-catenin pathway. In this study, we screened a library of aqueous extracts of 350 plants and identified Hovenia dulcis Thunb (HDT) extract as a Wnt/β-catenin pathway activator. HDT extract induced osteogenic differentiation of calvarial osteoblasts without cytotoxicity. In addition, HDT extract increased femoral bone mass without inducing significant weight changes in normal mice. In addition, thickness and area of femoral cortical bone were also significantly increased by the HDT extract. Methyl vanillate (MV), one of the ingredients in HDT, also activated the Wnt/β-catenin pathway and induced osteoblast differentiation in vitro. MV rescued trabecular or cortical femoral bone loss in the ovariectomized mice without inducing any significant weight changes or abnormality in liver tissue when administrated orally. Thus, natural HDT extract and its ingredient MV are potential anabolic agents for treating osteoporosis.